Natura costructa. Matematica e tecnica nella lettura bachelardiana di Spinoza - Zaltieri, Cristina (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2020)
The speech with which Bachelard paid homage to Spinoza in 1932, here became an opportunity for a comparison between the two materialistic thinkers on the main issues of mathematics and of technique. The comparison appears justified by the exemplary role attributed, in his text, by Bachelard to Spinoza as inspirator of the bachelardian concept of “phenomenotechnique”. Bachelard chooses to read the link of these two elements – operating in science – in the light of Spinoza’s natura naturans. The purpose that guides this article is not only to take a few steps in a comparison that is not easy and that has not so far been the subject of particular research, but also to show the originality of Bachelard’s use of Spinoza’s thought which anticipates interpretations of the late twentieth century. Keywords: Germ of crystallization, Natura constructa, Phenomenotechnique, Creative thought, Re- creation.